Polyethylene Glycol Fusion of Nerve Injuries: Review of the Technique and Clinical Applicability - Van Nest, Duncan S.; Kahan, David M.; Ilyas, Asif M. (Journal of Hand and Microsurgery, 2020)
Traumatic peripheral nerve injuries present a particular challenge to hand surgeons as mechanisms of nerve-healing pose serious limitations to achieving complete functional recovery. The loss of distal axonal segments through Wallerian degeneration results in the loss of neuromuscular junctions and irreversible muscle atrophy. Current methods of repair depend on the outgrowth of proximal nerve fibers following direct end-to-end repair or gap repair techniques. Investigational techniques in nerve repair using polyethylene glycol (PEG) nerve fusion have been shown to bypass Wallerian degeneration by immediately restoring nerve axonal continuity, thus resulting in a rapid and more complete functional recovery. The purpose of this article is to review the current literature surrounding this novel technique for traumatic nerve repair, paying particular attention to the underlying physiology of nerve healing and the current applications of PEG fusion in the laboratory and clinical setting. This article also serves to identify areas of future investigation to further establish validity and feasibility and encourage the translation of PEG fusion into clinical use.
Keywords: basic science; peripheral nerve repair; polyethylene glycol fusion; traumatic nerve injury